Phytochemical composition, antimicrobial and cytotoxicity activities of Parkia biglobosa (Jacq) benth extracts from Benin - Nounagnon, Martial; Dah-Nouvlessounon, Durand; N'TCHA, Christine; BABA-MOUSSA, FARID A. KADER SAÏD (My University, 2017)
Parkia biglobosa is a plant used in traditional medicine for the treatment of certain diseases. In order to scientifically appraise some of the anecdotal, folkloric ethno medical uses of P. biglobosa, this study aimed at making phytochemical screening and evaluating some biological activities of P. biglobosa leave and bark extracts. These organs powdered were used for qualitative phytochemical screening and extractions with 4 solvents (dichloromethane, ethyl acetate, ethanol and water). Total Polyphenols content were determined by spectrophotometer method. The antibacterial activity was tested on 10 references strains and 9 meat isolated Staphylococcus by disc diffusion method. The DPPH method was used to evaluate extracts antioxidant activity. Artemia salina larvae were used to evaluate the extracts cytotoxic effects. The major phytochemical constituent of interests such as polyphenol, glycosides are found to be present in the both organ. Leave ethanolic extract have total polyphenolic content three times higher than those of bark ethanolic extract. Whereas, total flavonoïd content was approximativly the same for the two extracts. Susceptibility of P. biglobosa extracts with the reference strains varies (p < 0.05) according to the strains and extracts. The ratio of the two parameters (CMI and CMB) shows that the bark extracts are more active on the reference strains with the same bactericidal power (54.14%). The leave ethanolic extract shows a highest value (17.86 ± 0.60 mM) of ascorbic acid as an antioxidant, while the bark ethanolic extract shows the lowest (14.28 ± 0.95 mM). These results confirm some uses of P. biglobosa in traditional medicine and pave the way for further studies.
Keywords: Extrait; Parkia biglobosa; produits carnés; Staphylococcus; activités biologique